The Influence of Strategic Leadership, Business Continuity Planning and Supply Chain Resilience on Organizational Performance: Instrument Validation - Habani, Mosaab A; Kamaruddin, Suzilawati (Business Management and Strategy, 2021)
Managing supply chain disruption needs to be considered an important activity for organizations. Supply chain risk management implies identifying, assessing, monitoring, and evaluating the potential risks across all supply chain members. The process of risk management emphasizes the improvement of supply chain performance through designing appropriate strategies. To be more precise, the chief responsibility in supply chain risk management is to ensure quality performance during crises and disruptions. Hence, identifying and validating risk-relevant factors that leads to superior business performance is necessary. This study aims to validate the instrument to measure the impact of factors associated with business performance i.e., strategic leadership, business continuity planning, and resilience to disruption. This paper contributes to the literature by developing a comprehensive model that strengthens a firm’s resilience to disruption and leads to superior business performance.